Evidence for distinguishable transcripts of the putative testis determining gene (ZFY) and mapping of homologous cDNA sequences to chromosomes X,Y and 9. - Affara, N A (1989)
Oligonucleotide sequences based on the amino acid sequence of the putative testis determining gene ZFY have been used to isolate a 1.3 Kb Hind III Y genomic DNA fragment CMPXY1 and three human testis cDNA sequences (CMPXY2, CMPXY3 and CMPXY4). These sequences detect at least four potential exons on the Y (Y1, Y3, Y4 and Y5), three on the X (X1, X2 and X3) and three of autosomal origin (A1, A2 and A3) as determined by comparing the fragments detected by different clones. Analysis with subfragments of CMPXY4 shows that Y3 is unique to the Y and that Y4 and X1 are homologous. Y5 and X3 are detected by the same subfragment of CMPXY4. This is also the case for Y1, X2, A1, A2 and A3. Thus these exons may contain further regions of homology between the X, Y and an autosomal locus. The X-linked sequences all lie in Xp21.2-Xp22.1 and studies with XX males have placed the Y-linked sequences in distal Yp adjacent to the Y-autosomal homologous sequence GMGY3. We have confirmed these localizations by in situ hybridization with CMPXY4 and have shown additionally that the autosomal sequences of both the CMPXY4 sequence and GMGY3 map to 9p22-9pter. Restriction analysis demonstrates that CMPXY1/XY2/XY3 differ in sequence from CMPXY4 at three restriction enzyme sites, thus suggesting that they are transcribed from different but closely related genes and that CMPXY4 must be either X-linked or autosomal in origin. This indicates that more than one of the loci containing ZFY-related sequences are transcribed and potentially fulfil functionally distinct roles in the human sex determining pathway. Northern blot analysis of human foetal testis RNA has shown that three low abundance transcripts of 5, 6 and 8 Kb can be detected by ZFY-related DNA sequences.